Cover, Content, and Editorial Note from Borneo J Pharm Vol. 6 No. 4 November 2023 - Borneo J Pharm, Chief Editor of (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm) has been published in November 2023. This edition contains ten articles: Analytical Pharmacy-Medicinal Chemistry, Pharmacology-Toxicology, Pharmaceutical, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from four countries: Costa Rica, India, Indonesia, and Sudan. The authors come from several institutions, including Universitas Airlangga, Matoshri College of Pharmacy, Universitas Pancasila, Universitas Indonesia, Universitas Borneo Lestari, Universitas Surabaya, Akademi Farmasi Yarsi Pontianak, Universidad de Costa Rica, Universitas Lambung Mangkurat, Universitas Padjadjaran, Omdurman Islamic University, and Universitas Sebelas Maret. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope all parties, especially the contributors, could re-participate for publication in the next edition in February 2024. Wassalamu’alaikum Wr. Wb.